P072: Comparing met vs. unmet palliative care needs in patients with end-stage conditions presenting to two Canadian emergency departments. (May 2019) - Garrido Clua, M.; Kruhlak, M.; Kirkland, S.; Villa-Roel, C.; Elwi, A.; O'Neill, B.; Brisebois, A.; Duggan, S.; Rowe, B.
Abstract : Introduction : Patients with end-stage conditions require integrated physical, spiritual, psychological and social care. Despite efforts to provide comprehensive community care, those with severe symptoms often present to emergency departments (EDs) with palliative care (PC) needs. The objective of this study was to identify patients with end-stage diagnoses presenting to EDs, and to document and compare their PC needs.Methods : A four-month prospective cohort study was conducted in two Canadian EDs. Using a modified PC screening tool, volunteer emergency physicians identified adult patients with end-stage illnesses and documented their PC needs. This tool has the ability to classify patients as having met vs. unmet PC needs based on the documentation of risk factors. Research assistants documented demographic information, severity at presentation (Canadian Triage and Acuity Scale CTAS), disposition and revisits from an electronic repository. Bivariate comparisons between patients with met vs. unmet PC needs were completed.Results : Overall, 663 patients were enrolled, of which 78% (n = 518/663) were identified as having unmet PC needs according to the screening tool. Cancer was the most prevalent condition in each group (43% unmet needs, 37% met needs). There was no significant difference between the two groups in terms of age, sex or CTAS score. The unmet PC needs group was more likely to be admitted (68% vs. 50%; p = 0.0001) when compared to patients with PC needs assessed as being met. No significant difference was noted in terms of time to physician assessment or ED length of stay. The two groups did not significantly differ in the proportion of return visits within 30 days (34% vs. 32%) or the average number of return visits (3 vs. 2 visits). A higher proportion of patients with unmet PC needs made at least one visit to the ED in the 6 months prior to their index visit compared to patients with met PC needs (74% vs. 51%, p < 0.001); yet, the average number of ED visits was similar between the groups (3 visits).Conclusion : This study revealed that patients with end-stage diagnoses, especially cancer, commonly have unmet PC needs. They are also more likely to present to the ED and to require hospitalization than patients in whom PC needs have been met. Further investigations into their clinical profile and health care utilization may clarify the impact of their unmet PC needs on the healthcare system.